Comparison of the polishing effects of polyetheretherketone materials under different chairside polishing systems - LIU Hengyan; LIU Yuchen; LI Kangjie; TIAN Min; NIU Lina; BAI Shizhu; FANG Ming (口腔疾病防治, 2023)
Objective The polishing effects of different compositions of chairside polishing systems on polyetheretherketone (PEEK) were compared to provide a reference for the rational selection of polishing systems for this material in clinical settings. Methods A total of 108 specimens were made from ShushijieTMPEEK crown and bridge materials, Bio-PAEK® dental PEEK, and BioHPP® PEEK. Thirty-six specimens of each material were randomly divided into 6 groups on average based on their polishing technique: OptiDisc®, Super-Snap® Rainbow Technique Kit, VITA ENAMIC®Clinical Polishing Set, Sof-LexTM Diamond Polishing System, Visio.lign Finishing Kit for Composite Veneers, and CERAMAGE Polishing Kit, LavaTM Ultimate ceramic and VITA ENAMIC ceramics were set as the control groups, and 6 specimens were made in each material, polished by Sof-LexTM Diamond Polishing System and VITA ENAMIC® Polishing Set clinical, respectively, according to the manufacturers’ suggestions. The surface roughness (Ra value and Sa value) and gloss of each set were measured. The surface morphologies of the polished specimens were observed by scanning electron microscopy. Results Surface roughness (Ra value and Sa value) and gloss were mainly influenced by the type of polishing system, and they varied between PEEK material types. The Sof-LexTM Diamond Polishing System produced the highest surface roughness and the lowest gloss values for PEEK materials, while the Super-Snap® Rainbow Technique Kit, Visio.lign Finishing Kit for Composite Veneers and CERAMAGE Polishing Kit resulted in low surface roughness values. The Visio.lign Finishing Kit for Composite Veneers and CERAMAGE Polishing Kit exhibited high gloss values. Polishing paste particles were observed embedded on the surfaces of the PEEK materials polished by the Visio.lign Finishing Kit for Composite Veneers; the surfaces of specimens polished by the CERAMAGE Polishing Kit were smooth, without polishing paste particle residue. Using the same polishing system, the best polishing results were obtained with BioHPP® among the PEEK materials tested. The surface roughness values of the three tested PEEK materials polished by the CERAMAGE Polishing Kit were similar to those of the LavaTM Ultimate ceramic and VITA ENAMIC ceramic, but the gloss was higher than that of both. Conclusion CERAMAGE Polishing Kit was recommended for polishing all three tested PEEK materials, achieving a good polishing effect, with similar surface roughness and higher gloss characteristics comparable to those of polished computer-aided design and manufacturing (CAD/CAM) resin-matrix ceramics.